Pengembangan Sistem Informasi Desa Dalam Upaya Penanggulangan Kemiskinan Di Desa Rarang Selatan - Annisa, Meita; Laksmono, Bambang Shergi (UI Scholars Hub, 2023)
Indonesia continues to face challenges in poverty alleviation, with extreme poverty still prevalent in the country. Despite having a social protection system aimed at reducing poverty and cushioning the poor and vulnerable from crises, its implementation often encounters difficulties, particularly in obtaining valid and verified data sources. This study explores how the development of the Village Information System (SID) can contribute to poverty alleviation in Rarang Selatan Village, West Nusa Tenggara Province (NTB). When SID was introduced in 2016, Rarang Selatan was a newly established village classified as underdeveloped. By 2022, the village had progressed to the category of an independent village. This research employs a qualitative method with a descriptive design, gathering data through document studies, observations, and in-depth interviews. Informants include Rarang Selatan Village officials and several related Regional Apparatus Organizations, as well as community of Rarang Selatan. All interviews were conducted face-to-face at the respective locations of the informants. The findings reveal that SID assists the village in managing population data and ensuring that all residents have necessary civil documents. SID also supports village planning and budgeting, including the distribution of aid and improving service efficiency. However, despite achieving independent village status, many people in this village are reluctant to relinquish their poverty status to continue receiving various government social assistance programs.